Free wifi giving a voice to the community: a case of the Johannesburg public wifi in Soweto - Mnisi, N (My University, 2019)
Various authorsi have warned against the assumption that mere access to the internet by disadvantaged communities will automatically yield active citizens, participation and voice. This thesis focuses on uncovering the extent to which availability of free public wifi in a disadvantaged community can enable a voice for that community. This research, conducted at three wifi hotspots uses a mixed methods approach, with a questionnaire for quantitative analysis and observation for qualitative as the data collection methods. The findings of the research indicate that despite the government's efforts to get the Soweto community online through free wifi provision, key disadvantaged stakeholders in the community remain excluded. These include women, people over 40 years of age and older, the disabled and people who are too old or sickly to walk to the free wifi zones. However, the findings also suggested that the advantage of social media for community members lies in its ability to connect people to the decision makers directly, rather than reliance on a third party or mediator to receive feedback on issues raised. The findings suggest that community members who engage with government officials aim to solve issues relating to provision of basic services in many cases. Overall, the findings point to an incongruity between the expectations of what free public wifi can offer in terms of improving the well-being of disadvantaged communities, and the lived reality of those communities
Keywords: Wireless Internet--South Africa; Telecommunication; Internet telephony--South Africa